Amyloid goitre and hypothyroidism secondary to cystic fibrosis. Issue 835 (May 1995) - Alvarez-Sala, R.; Prados, C.; Sastre Marcos, J.; García Río, F.; Vicandi, B.; de Ramón, A.; Villamor, J.
Abstract : Although cystic fibrosis (CF) is still the most frequently fatal childhood disease, many adults now survive into their third and fourth decades. Uncommon complications of chronic diseases, such as amyloidosis, while infrequent, may now appear during the course of CF in adulthood. We present a case of a patient with CF who was diagnosed with hypothyroidism due to amyloid deposits in the thyroid.